Tujuan Pendidikan Islam dalam Mencetak SDM Unggul - Mila Mahmudah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2020)
Since the beginning of the development of Islamic education has stood upright on two very important basic sources namely the Al-Quran and the sunnah of the prophet in the sacred scripture contained verses of mufasshalat (detailed) and verses of mubbayyinat (which provide proof of truth) that encourage humans to study and write and to study, think about and analyze the creation of heaven and earth. Islam since its inception shows the importance of education for human life. The first verse received by the prophet Muhammad is iqro